Effect of the Pt concentration on microstructures of Ti-Pt alloys using the first-principles phase field method. (15th August 2021) - Pham, Thi Nu; Ohno, Kaoru; Sahara, Ryoji; Kuwahara, Riichi; Bhattacharyya, Swastibrata
Graphical abstract: Abstract: The effect of the Pt concentration on microstructures of Ti-Pt alloys is studied by the first-principles phase field (FPPF) method, which enables us to investigate the evolution of microstructures from first principles without using thermodynamic empirical parameters. The method first constructs the local free energy, which is needed in the phase field simulation, by combining density functional theory, cluster expansion theory including atomic vacancies, and potential renormalization theory. Applying this FPPF method to Ti 1 − x Pt x alloys at 800 ∘ C, we have confirmed that increasing the Pt concentration as 5, 10, 15 and 20 wt% causes a drastic change in the microstructure of Ti-Pt alloys in accord with the experimental observation by Song et al. (Materials 7 (2014) 3990). In the case of the Pt concentration less than 10 wt%, the microstructure is lamellar- or wavy-shaped everywhere. When the Pt concentration is 15 and 20 wt%, spot-like Ti 3 Pt precipitates appear in the α -Ti phases with lamellar- or wavy-shaped patterns. These results are confirmed in both 2D and 3D simulations.